CIVIL LEGAL ASPECTS IN INSURANCE AGREEMENTS (RESEARCH STUDY OF PT PRUDENTIAL LIFE ASSURANCE) - Robby Tandean Oei; Bambang Fitrianto; Hasdiana Juwita Bintang (Journal of International Islamic Law, Human Right and Public Policy, 2025)
This study discusses life insurance products accompanied by long-term investments from PT Prudential Life Assurance, which offers protection for insured by considering high risks related to market fluctuations and global economic uncertainty. This insurance product requires an in-depth understanding related to the legal arrangements for the insured, the legal liability of the insurance company in fulfilling claims, and the dispute resolution mechanism between the two parties. Therefore, it is important to research various legal aspects related to the implementation of life insurance products, especially those related to claim obligations, dispute resolution, and the difference between sharia and conventional insurance premiums. The formulation of the problem in this study is how the legal arrangements relate to life insurance products and what are the forms of legal liability that must be fulfilled by insurance companies in the claims process. This study aims to: 1) analyze the form of legal protection of the insured in the payment of life insurance claims, 2) examine the responsibility of insurance companies in the payment of life insurance claims, and 3) compare the form of dispute resolution and the difference between sharia and conventional insurance premiums. The methods used in this study are normative juridical approaches and empirical juridical approaches. The normative juridical approach is used to analyze legal provisions relevant to life insurance products, be it laws and regulations, agreements in insurance policies, or legal principles that govern legal protection for the insured. An empirical juridical approach is used to dig into data from practice in the field, which involves interviews with relevant parties in insurance companies and analysis of cases related to insurance claims. The data used in this study consisted of: 1) company policy documents and insurance policies, 2) laws and regulations governing the life insurance industry, 3) interviews with parties involved in the claims mechanism and dispute resolution, and 4) case studies related to insurance claims. The conclusion of this study shows that: 1) Legal protection for the insured in the payment of life insurance claims has been regulated in the applicable legal provisions, both through laws and regulations and clauses in the insurance policy, 2) The responsibility of insurance companies in the payment of claims is strictly regulated in the Consumer Protection Law, the Civil Code, and the Law on Insurance Business, 3) The settlement of insurance claims disputes is generally carried out through institutions Arbitration is in accordance with the terms of the policy, but can also be conducted through legal channels if there are no arbitration clause. The difference between sharia and conventional insurance premiums lies in the legal basis and the fund management mechanism, although both have similar basic principles in terms of legal protection for the insured.